Adopting online flipped teaching to improve learner engagement in an English for specific purposes (ESP) course in China: a mixed-methods study - Li Zhiyong; Wang Yang (Journal of China Computer-Assisted Language Learning)
In this study, we evaluated the effect of online flipped teaching on learner engagement in an English for specific purposes (ESP) listening and speaking course at a Chinese university. We also aimed to understand the factors influencing learner engagement in an online environment. For this study, an e-learning platform called Yunbanke was used for asynchronous teaching in a flipped class, and Tencent Meeting was employed for synchronous teaching in the non-flipped and flipped class, respectively. We used a mixed-methods approach. First, we conducted a quasi-experiment to compare engagement levels between the experimental group (flipped class, n = 34) and control group (non-flipped class, n = 35) before and after 16 weeks of online instruction. Then, we used lesson logs and conducted interviews with the students and the instructor. The results showed that online flipped teaching could significantly improve the learners’ behavioural and cognitive engagement compared to the non-flipped class. However, no significant difference was found in emotional engagement between the two classes. Qualitative data supported our quantitative findings, and five key factors leading to different dimensions of learner engagement were identified: learners’ prior English attainment, learners’ perceived affordance of online learning and teaching, interpersonal factors, instructor presence and learning tasks. Our findings can shed light on online ESP learners’ engagement and improve online ESP teaching practices.